Comparison of innate immune responses towards rhinovirus infection of primary nasal and bronchial epithelial cells. Issue 2 (26th November 2015) - Alves, Marco P.; Schögler, Aline; Ebener, Simone; Vielle, Nathalie J.; Casaulta, Carmen; Jung, Andreas; Moeller, Alexander; Geiser, Thomas; Regamey, Nicolas
Abstract: Background and objective: Rhinoviruses (RV) replicate in both upper and lower airway epithelial cells. We evaluated the possibility of using nasal epithelial cells (NEC) as surrogate of bronchial epithelial cells (BEC) for RV pathogenesis cell culture studies. Methods: We used primary paired NEC and BEC cultures established from healthy subjects and compared the replication of RV belonging to the major (RV16) and minor (RV1B) group, and the cellular antiviral and proinflammatory cytokine responses towards these viruses. We related antiviral and pro‐inflammatory responses of NEC isolated from CF and COPD patients with those of BEC. Results: RV16 replication and major group surface receptor (ICAM‐1) expression were higher in healthy NEC compared with BEC ( P  < 0.05); RV1B replication and minor group surface receptor (LDLR) expression were similar. Healthy NEC and BEC produced similar levels of IFN‐β and IFN‐λ2/3 upon RV infection or after simulation with poly(IC). IL‐8 production was similar between healthy NEC and BEC. IL‐6 release at baseline ( P  < 0.01) and upon infection with RV16 ( P  < 0.05) and poly(IC) stimulation ( P  < 0.05) was higher in NEC. RV1B viral load in NEC was related to RV1B viral load in BEC (r = 0.49, P  = 0.01). There was a good correlation of IFN levels between NEC and BEC (r = 0.66, P  = 0.0004 after RV1B infection). IL‐8 production in NEC was related to IL‐8 production in BEC (r = 0.48, P  = 0.02 after RV1B infection). Conclusion: NEC are a suitable alternative cellular system to BEC to study the pathophysiology of RV infections and particularly to investigate IFN responses induced by RV infection. Abstract : We evaluated the use of nasal epithelial cells (NEC) as surrogate of bronchial epithelial cells (BEC) for rhinovirus (RV) studies. We found that NEC are a suitable alternative cellular system to BEC to study the pathophysiology of RV infections and particularly to investigate interferon responses induced by RV infection.